Risk quantification in coal procurement for power generation: The development of Supply Shortage Impact matrix - Ibrahim J.A.; Hashim A.H.; Majid M.; Tahar R.M. (2023)
Systems are secure if its have lower risks of system interruption. However, to determine the optimum level of security is an area where requires more research. In principle, the optimum level of security that a system provides is determined by the interaction between the cost of providing extra security and the value to consumers. The risks in energy system have to be quantified in order to identify the level of security. To make comparison between the cost of providing energy security and level of security, the quantified risks have to be in the same common variable as the costs. Then, an optimum level of security and cost can be estimated using appropriate methods. As no such attempts have been tried to compare the risks and the cost in the same platform, it is difficult to determine the optimum security point between the risks and cost of providing that security. The objective of this paper is to present the development of Supply Shortage Impact for risk quantification in coal procurements for power generation. This method in combination with Non-delivery Probability Table will provide risk in common variable as the cost for presenting valuable information on security and cost of providing it. 2010 IEEE.